LncRNA Chaer Prevents Cardiomyocyte Apoptosis From Acute Myocardial Infarction Through AMPK Activation - He, Zhiyu; Zeng, Xiaojun; Zhou, Deke; Liu, Peiying; Han, Dunzheng; Xu, Lingling; Bu, Tong; Wang, Jinping; Ke, Mengmeng; Pan, Xiudi; Du, Yipeng; Xue, Hao; et al. (Frontiers in Pharmacology, 2021)
Rationale: Worldwide, ischemic heart disease (IHD) has been considered to be the leading cause of death. Among IHD, the most prevalent manifestation is acute myocardial infarction (AMI) associated with cardiac cell death. The apoptotic process has a key role in the myocardial loss in the initial phase of AMI and participates in the subsequent left ventricular remodeling, leading to symptomatic cardiac failure. Various studies suggest that lncRNA is a powerful cardioprotective regulator in cardiovascular diseases via inhibiting the cardiomyocytes apoptosis and reduce infarction area in mice, serve a protective effect on cardiac AMI injury. LncRNA Chaer regulates cardiac hypertrophy, although, its role in the initial phases of AMI remains elusive. Objective: To evaluate the influence of lncRNA Chaer in cardiomyocytes' response to AMI via in-vitro and in-vivo approaches. Methods and Results: Simulated AMI injury to cultured neonatal mice cardiac myocytes (NMCMs) with hypoxia exposure induced apoptotic cell death. Overexpression of lncRNA Chaer in cardiomyocytes significantly protected cardiomyocytes from OGD-induced apoptosis, while knockdown of lncRNA Chaer increased cardiomyocyte apoptosis, induced by OGD. Moreover, cardiomyocytes' specific overexpression of lncRNA Chaer ameliorated AMI injury in-vivo. Exploration of underlying mechanisms suggested that lncRNA Chaer mitigates cardiomyocytes apoptosis by promoting the activation of AMPK. Conclusions: LncRNA Chaer could attenuate cardiomyocytes apoptosis, at least in part, although it can promote the phosphorylation of AMPK.